Effectiveness of Mobile Apps in Second Language Acquisition (Texas Journal of Philology, Culture and History, 2025)
This article explores the effectiveness of mobile applications in second language acquisition (SLA) in the context of modern technological advancements. With the growing demand for learning foreign languages, mobile apps such as Duolingo, Memrise, Babbel, and Rosetta Stone have become valuable tools for learners worldwide. The study highlights key advantages of these apps, including their flexibility, accessibility, personalized learning features, and interactive nature. It also discusses how mobile apps support the development of all four language skills—listening, speaking, reading, and writing—and assist learners in preparing for international exams like IELTS. Furthermore, the paper refers to educational theories such as Krashen’s Input Hypothesis and Vygotsky’s ZPD to explain the pedagogical effectiveness of these tools. Social and collaborative aspects of language learning apps are also examined, emphasizing real-time communication with other learners. While acknowledging some , the paper concludes that mobile applications are essential supplements in language learning, especially in today’s digital age .